2022
DOI: 10.1016/j.jbc.2022.101685
|View full text |Cite
|
Sign up to set email alerts
|

LPGAT1 controls the stearate/palmitate ratio of phosphatidylethanolamine and phosphatidylcholine in sn-1 specific remodeling

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…As mentioned above, LPLAT7 was shown to have a role in determining the stearate-to-palmitate ratio in PL species ( 22 ). Our lipidomic analyses showed that loss of LPLAT7 increased not only C16:0-containing PLs but also C18:1-containing PLs ( Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As mentioned above, LPLAT7 was shown to have a role in determining the stearate-to-palmitate ratio in PL species ( 22 ). Our lipidomic analyses showed that loss of LPLAT7 increased not only C16:0-containing PLs but also C18:1-containing PLs ( Fig.…”
Section: Discussionmentioning
confidence: 96%
“…They also demonstrated that LPLAT7/LPGAT1 preferred sn -2-acyl LPE over sn -1-acyl LPE using a recombinant enzyme expressed in E. coli . They claimed that LPLAT7/LPGAT1 had no LPLAT activity against LPC ( 22 ). The result is incompatible with our present results, which we discuss below.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PS having oleic acid (18:1) at the sn- 2 position interacts with cholesterol when its sn- 1 acyl chain is stearic acid (18:0), but not palmitic acid (16:0) 22 . The enzyme LPGAT1 was shown to remodel GPLs, especially PE, to increase 18:0 levels at the sn- 1 position, and its deficiency is partially lethal 23,24 . The existence of LPGAT1 as a regulator of 18:0 in PE might also explain why GPAT4 mutants had no changes in this acyl chain for PE, in contrast to PC, PI, and PS.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently shown that lysophosphatidylglycerol acyltransferase 1 (LPGAT1) is a key remodeling enzyme located in the ER and involved in the regulation of the stearate/palmitate ratio at the sn1 position of LysoPE species. 37 It is possible that LPGAT1 is responsible for the 15 N-PE16:0-13 C18:1 (i.e. 15 N 13 C-PE34:1) remodeling into 15 N-PE18:0-13 C18:1.…”
Section: Discussionmentioning
confidence: 99%